Contemporary theory and practice in counseling and psychotherapy - Tinsley, Howard E. A.; Lease, Suzanne H.; Wiersma, Noelle S. (Los Angeles : Sage, 2016)
This comprehensive, topically arranged text provides a contemporary account of counseling theories as practiced by internationally acclaimed experts in the field. Each chapter covers the way mindfulness, strengths-based positive psychology, and the common factors model are integrated into the theory. A special emphasis on evidence-based practice helps readers prepare for their work in the field. From back cover.
Contemporary approaches to counseling and psychotherapy -- Sigmund Freud, Carl Jung, and the genesis of psychotherapy -- Evidence-based practice in psychology: what psychotherapists can learn from research on treatment and psychotherapist responsiveness -- Adlerian psychotherapy -- Psychodynamic psychotherapy -- Behavior modification -- Reality therapy -- Dialectical behavior therapy -- Rational emotive behavior therapy (REBT) theory and practice -- Cognitive-behavioral approaches in counseling and psychotherapy -- Person-centered therapy -- Existential therapy: confronting life's ultimate concerns -- Coherence therapy: the roots of problems and the transformation of old solutions -- Narrative therapy: language and stories in counseling and psychotherapy -- Contemporary gestalt therapy: an early case of theoretical integration come of age -- Integrative theories of psychotherapy -- Developing a personal theoretical orientation.
Includes bibliographical references and index.
Keywords: Counseling; Psychotherapy